PENERAPAN METODE PROJECT BASED LEARNING BERMUATAN IPTEK DALAM MATA KULIAH PENULISAN BAHAN AJAR - Sary Sukawati; R Mekar Ismayani; Aditya Permana (STKIP Siliwangi, 2019)
Education in the Industrial Age 4.0 utilizes advances in science and technology (IPTEK), especially the internet. Learning no longer has to be done in the classroom face to face. All can be done online. As a student at a teacher training college that will produce prospective teachers (educators) must have professional competence. This is non-negotiable, in addition to three other competencies. One indicator of professional competence is being able to compile teaching materials. Therefore, as one of the efforts to improve the ability of students to write teaching materials, a study was carried out applying the method of learning based on science and technology-based learning to adjust to this internet era. This study uses an experimental method with a one-shot case study design. The research sample of regular students of the Indonesian Language and Literature Education Study Program IKIP Siliwangi who are contracting a course in writing teaching material. The results of writing teaching materials student work uploaded through the google classroom application. The results showed the highest student score was located in aspect 2, namely the content of teaching materials. While the lowest aspect is aspect 3, which is the use of grammar in teaching materials. Even so, the final average obtained overall shows a value of 81.8. This value is in the very good range. Thus it can be concluded that the application of Project-Based Learning Method with Science and Technology Effectiveness is effective in learning to write teaching materials.